Appropriateness of Medications in Older Adults Living With Frailty: Impact of a Pharmacist-Led Structured Medication Review Process in Primary Care - Sheny Khera; Marjan Abbasi; Julia Dabravolskaj; Cheryl A. Sadowski; Hannah Yua; Bernadette Chevalier (SAGE Publishing, 2019)
Background: Older persons with frailty take multiple medications and are vulnerable to inappropriate prescribing. Objective: This study assesses the impact of a team-based, pharmacist-led structured medication review process in primary care on the appropriateness of medications taken by older adults living with frailty. Methods: This was a quasi-experimental pretest-posttest design in 6 primary care practices within an academic clinic in Edmonton, Alberta, Canada. We enrolled community dwelling older adults 65 years and older with frailty who have polypharmacy and/or 2 or more chronic conditions (ie, high-risk group for drug-related issues). The intervention was a structured pharmacist-led medication review using evidence-based explicit criteria (ie, Beers and STOPP/START criteria) and implicit criteria (ie, pharmacist expertise) for potentially inappropriate prescribing, done in the context of a primary care team-based seniors' program. We measured the changes in the number of medications pre- and postmedication review, number of medications satisfying explicit criteria of START and STOPP/Beers and determined the association with frailty level. Data were analyzed using descriptive and inferential statistics (a priori significance level of P < .05). Results: A total of 54 participants (61.1% females, mean age 81.7 years [SD = 6.74]) enrolled April 2017 to May 2018 and 52 participants completed the medication review process (2 lost to hospitalization). Drug-related problems noted on medication review were untreated conditions (61.1%), inappropriate medications (57.4%), and unnecessary therapy (40.7%). No significant changes in total number of medications taken by patients before and after, but the intervention significantly decreased number of inappropriate medications (1.15 meds pre to 0.9 meds post; P = .006). Conclusion: A pharmacist-led medication review is a strategy that can be implemented in primary care to address inappropriate medications.